Peran BAZNAS dalam Mengurangi Pengangguran Melalui Zakat Produktif: Kajian Systematic Literature Review - Rizki Pratiwi Harahap (Journal of Islamic Social Finance Management, 2026)
Unemployment remains one of the major economic and social issues in Indonesia, including Padangsidimpuan City. Productive zakat is recognized as an instrument of economic empowerment that promotes the economic independence of mustahik (zakat beneficiaries) and contributes to unemployment reduction. This study aims to examine the role of the National Zakat Agency (BAZNAS) of Padangsidimpuan City in reducing unemployment through productive zakat-based economic empowerment programs. This study employed the Systematic Literature Review (SLR) method by reviewing relevant scientific articles, national journals, and previous studies. The findings indicate that productive zakat programs, such as business capital assistance, the provision of production facilities, and microenterprise development, have contributed to improving beneficiaries' productivity, increasing their income, and creating self-employment opportunities. However, the effectiveness of these programs is constrained by limited business mentoring, inadequate program monitoring, and the low managerial capacity of some beneficiaries. Therefore, strengthening entrepreneurship training, continuous mentoring, and regular program evaluation is essential to optimize the impact of productive zakat on unemployment reduction. This study concludes that productive zakat has considerable potential as an instrument for economic empowerment and sustainable unemployment reduction.